Mapping potential zones for groundwater recharge and its evaluation in arid environments using a GIS approach: Case study of North Gafsa Basin (Central Tunisia). (May 2018) - Mokadem, Naziha; Boughariou, Emna; Mudarra, Matías; Ben Brahim, Fatma; Andreo, Bartolome; Hamed, Younes; Bouri, Salem
Abstract: With the progressive evolution of industrial sector, agricultural, urbanization, population and drinking water supply, the water demand continuously increases which necessitates the planning of groundwater recharge particularly in arid and semi-arid regions. This paper gives a comprehensive review of various recharges studies in the North Gafsa basin (South Tunisia). This latter is characterized by a natural groundwater recharge that is deeply affected by the lack of precipitations. The aim of this study is to determine the recharge potential zones and to quantify (or estimate) the rainfall recharge of the shallow aquifers. The mapping of the potential recharge zones was established in North Gafsa basin, using geological and hydrological parameters such as slope, lithology, topography and stream network. Indeed, GIS provide tools to reclassify these input layers to produce the final map of groundwater potential zones of the study area. The final output map reveals two distinct zones representing moderate and low groundwater potential recharge. Recharge estimations were based on the four methods: (1) Chloride Method, (2) ERAS Method, (3) DGRE coefficient and (4) Fersi equations. Therefore, the overall results of the different methods demonstrate that the use of the DGRE method applying on the potential zones is more validated. Highlights: To characterize the hydrodynamic functioning of the shallow aquifers. To determine the potential zones for groundwater recharge. To estimate the natural recharge. To investigate the groundwater in the semi-arid region (Gafsa region).